INTEGRASI KONSEP WATERFRONT PADA PERENCANAAN KAWASAN BANTARAN SUNGAI LEMBEH DI KABUPATEN TOLITOLI - M Alif; Dwi Purnomo; Mansur S Pahude (Tolis Ilmiah : Jurnal Penelitian, 2026)
Riverbank settlement arrangement in urban areas often faces challenges of density, environmental degradation, and flood risks due to uncontrolled space utilization. This study aims to formulate a spatial arrangement concept through a waterfront approach that functions as a flood mitigation system while improving environmental quality. The method used is descriptive-qualitative with a contextual design approach based on the analysis of existing conditions, housing patterns, and community space needs. The design results show that the waterfront concept can be implemented by managing river borders as green open absorption spaces, implementing adaptive housing, providing public pedestrian paths, and integrating drainage systems. This arrangement successfully creates an area that is safer from flood risks, improves the quality of living space, and establishes a sustainable functional relationship between human activities and the river.